Tie Strength in GitHub Heterogeneous Networks - Oliveira, Gabriel P.; Batista, Natércia A.; Brandão, Michele A.; Moro, Mirella M. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2018)
In social networks, the relationship between individuals is defined by many forms of interaction. Here, our goal is to measure the strength of the relationship between GitHub users by considering social and technical features. Thus, we model GitHub's heterogeneous collaboration network with different types of interaction and propose new metrics to the strength of relationships. The results show the new metrics are not correlated, bringing new information to the table. Finally, these metrics may become important tools to determine users' influence and popularity.